Intestinal‐type sinonasal adenocarcinomas: The road to molecular diagnosis and personalized treatment. Issue 10 (25th May 2016) - Hoeben, Ann; van de Winkel, Linda; Hoebers, Frank; Kross, Kenneth; Driessen, Chantal; Slootweg, Pieter; Tjan–Heijnen, Vivianne C. G.; van Herpen, Carla
Abstract: Background: Sinonasal intestinal‐type adenocarcinomas (ITACs) are epithelial tumors of the nasal cavity and the paranasal sinuses, often related to professional exposure to organic dust, mainly wood or leather. It is a rare cancer. If resectable, surgery is the treatment of choice. Postoperative radiotherapy is often indicated to increase local control. Systemic treatment (chemotherapy, targeted agents, or immunotherapy) of irresectable ITACs and/or metastasized disease is less standardized. Methods: Articles on ITAC histopathology, molecular profile, and current treatment options of this specific tumor were identified and reviewed, using the electronic databases Pubmed, Medline, Cochrane, and Web of Science. Results: This article reviews what is currently known on the histopathology, tumorigenesis, molecular characteristics, and standardized treatment options of ITAC. Conclusion: More translational research is needed to identify druggable targets that may lead to a personalized treatment plan in order to improve long‐term outcome in patients with locally advanced and/or metastasized ITAC. © 2016 Wiley Periodicals, Inc. Head Neck 38: First–1570, 2016